Optimization of Flow Injection (FI) – Spectrophotometry for Hydroquinone Analysis - Muhammad Iqbal Fahmi; Hermin Sulistyarti; Ani Mulyasuryani; Adam Wiryawan (The Journal of Pure and Applied Chemistry Research, 2019)
Hydroquinone is one of the phenolic compounds used in various cosmetic products for skin lightening as it can inhibit tyrosinase enzyme in producing melanin. However, hydroquinone is classified as a toxic compound, therefore, several countries such as Africa, Canada, and Indonesia prohibits hydroquinone usage in cosmetics. This research was focused on the development of a method for hydroquinone analysis using flow injection (FI) combined with spectrophotometry based on the reaction of hydroquinone with phloroglucinol in alkaline condition producing orange complex detected at 493 nm. The FI method was optimized based on operational factors and chemical factors in order to achieve sensitivity. The maximum sensitivity of FI method was achieved under operational condition of 100 μL sample volume, 100 cm mixing coil 1, 50 cm mixing coil 2 and 2.8 mL/min with the chemical condition of 0.005 mol/L NaOH and 0.001 mol/L phloroglucinol. Under these optimum conditions, the proposed method showed linearity in the range concentration of 2 – 80 mg/L and the method was applied to cosmetic sample with acceptable recovery